PENGARUH PERBANDINGAN TANAH DAN SERBUK ARANG TEMPURUNG KEMIRI SEBAGAI MEDIA TUMBUH TERHADAP PERTUMBUHAN SEMAI KEMIRI (Aleurites moluccana Willd) - Harsono, Dedi; Yusran, .; Umar, Husain (Jurnal Warta Rimba, 2018)
Candlenut (Aleurites moluccana Willd) is one of the industrial plants which has economic value and it can be developed in Indonesia. The development of candlenut plants in Indonesia needs to get attention because until now the technology of candlenut cultivation is still very simple and still lack high-quality seeds. Therefore, a study was conducted to find out the effect on the growth of candlenut seedling toward soil comparisons and shell charcoal powder with some comparisons of growing seedling. This study used Completely Randomized Design (RAL), which consists of 6 comparative treatments are (P0) 100% soil and 0% charcoal/control, (P1) 90% soil and 10% charcoal, (P2) 80% soil and 20% charcoal, (P3) 70% soil and 30% charcoal, (P4) 60% soil and 40% charcoal, (P5) 50% soil and 50% charcoal with 5 replications so that overall there are 30 samples of plant experiment. Parameters that is observed include high growth, stem diameter increased, number of leaves, dry weight of roots and canopy, and seed quality index. The result showed that the treatment of soil comparative and shell charcoal powder as growing media on the growth of candlenut seedling (Aleurites molucana Willd) gives very significant effect of high growth, stem diameter, number of leaves, canopy dry weight, root dry weight, and quality index of candlenut seedling compared with the control one. The best treatments are (P3) comparison of 70%Â  soil and 30% charcoal..Keywords: level of comparisons, Soil, Shell Charcoal Powder Of Candlenut, Candlenut Seedling.